Impact of job location on relationship between job satisfaction and self‐esteem of employees: Evidence from the Indian BPOs. Issue 2 (2nd September 2019) - Sam, Mani P.; Khan, Imran Ahmed; Babu, Deepak
Abstract : Does job location impact on job satisfaction and self‐esteem? To answer this question, a sample of 298 responses was drawn from business process outsourcing employees working in four different locations in two south Indian states. The study conducted in both rural and urban locations witnessed that the job location (rural/urban) has a significant impact on job satisfaction and self‐esteem despite similar job demands and resource support conditions for all the respondents. Results show a very large divergence in self‐esteem between rural and urban settings and some divergence across genders. Location of delivery centres in smaller towns could thus be an effective solution for the high turnover experienced at urban delivery centres handling data capture and such low end processing.